Assessment of food allergies in patients under two years of age with skin manifestations referred to pediatric immunology and allergy outpatient clinic - Ünsal, Hilal; Akalin Ertürk, Beyza (The European Research Journal, 2025)
Objectives: In the first two years of life, patients with cutaneous manifestations with suspicion of food allergy are frequently referred to clinicians in daily practice. The aim of this study was to investigate the frequency of food allergy (FA) in infants presenting with cutaneous manifestations. Methods: Patients aged <2 years with suspected food allergy and cutaneous manifestations who were admitted to the pediatric immunology and allergy outpatient clinic at Sincan Training and Research Hospital were included. Demographic, clinical and laboratory features of patients were recorded. The severity of atopic dermatitis (AD) was classified using the SCORing AD index. Results: The study included 217 children with a median age of 9.7 months (IQR 5.8-13.6) (55.8% males). AD (77.9%) was the most common skin manifestation in all patients. Other cutaneous manifestations were urticaria/angioedema (12.4%) and flushing (9.7%). 23 (13.6%) patients were classified as moderate-severe AD and 146 (86.4%) patients as mild AD. The age at diagnosis is lower in the moderate-severe AD group [9 months (IQR 4-15)] compared to the mild AD group [14 months (IQR 9-18)] (P=0.011). In all AD patients, food allergy was detected in 54 (32%) patients. The percentage of food allergy was higher in the moderate-severe AD group (82.6%) than in the mild AD group (24%) (P<0.001). Multiple FA was shown in 13 (7.7%) patients and the percentage of Multiple FA was higher in the moderate-severe AD group (21.7%) than in the mild AD group (5.5%) (P=0.018). When the most common food allergies were compared, hen’s egg and cow’s milk allergy were found to be higher in the moderate-severe AD group [(56.5%) vs. (47.8%)] than in the mild AD group [(18.5%) vs. (9%)] (P<0.001 and P<0.001, respectively). Forty oral food challenges (OFC) tests were performed on patients who were found to have food sensitivity and all passed. In 58 (26.7%) patients, food allergy was identified and food elimination was started. In 54 (24.8%) patients with AD culprit food was eliminated from the diet. No food allergy was found in any patient presenting with flushing. Cow’s milk allergy was found in two patients and hen’s egg allergy in two patients who presented with urticaria. Conclusions: We identified food allergy in only one out of every four patients presenting with suspected food allergy and cutaneous manifestations. Correct evaluation of hypersensitivity reactions to foods is important to avoid unnecessary food elimination from infants’ diet.